Pengaruh Self Efficacy Dan Dukungan Sosial Terhadap Student Well Being Di SMA N 4 Karawang - Randwitya Ayu Ganis Hemasti; Nur Ainy Sadijah; Ahmad Paisal Gojali; Kurnia Pratiwi (Departement of Mathematics Education, 2024)
Improving the quality of human resources is one of the emphasis of educational goals. High school students in their developmental stage are classified as teenagers. According to Santrock (2011) there are several problems experienced by adolescents in fulfilling developmental tasks in adolescence, namely personal problems and typical adolescent problems. Teenagers today get a lot of pressures starting from environmental and socio-cultural conditions as well as the self-development of the teenagers themselves.This study aims to determine the effect of self-efficacy and peer social support on student well-being at SMAN 4 Karawang. In this study there are three variables, namely Self Efficacy, peer social support, and student well-being. The major hypothesis of this study is that there is an influence of Self Efficacy and peer social support on student well-being at SMA N 4 Karawang. Self-efficacy is a learning strategy in which students are metacognitively motivated or driven to learn and actively participate in the independent learning process. Peer social support is an individual's assessment of positive assistance or support received from friends whose level of maturity or age is more the same, so that individuals feel valued, cared for, and loved (Simanjuntak & Indrawati, 2019). The number of samples used was 177 students at SMA N 4 Karawang. Using purposive sampling method. The data method in this study uses a quantitative method. The analysis in this study used multiple regression analysis using SPSS 22.0.